Modelling, verification and analysis of articulated steer vehicles and a new way to eliminate jack-knife and snaking behaviour. (29th July 2019) - Gao, Yu; Shen, Yanhua; Yang, Yaodong; Zhang, Wenming; Güvenç, Levent
A non-linear articulated steer vehicle (ASV) model coupled by 12-DOF (degrees-of-freedom) dynamic model and full-hydraulic steering system model is derived. Field tests of single-lane change are made to verify the accuracy of ASV model. Considering the effect of varying bulk modulus, the unstable area of ASV decided by oil pressure and air content is confirmed. To reveal the differences between the non-linear vehicle model and the linear vehicle model, articulation angle responses of the two models are compared. Results show that the non-linear vehicle model has a smaller unstable area than the linear model, which means the non-linear model is less sensitive to disturbance than the linear model. A new way to improve the stability of ASV by filling-oil pressure control is presented. Simulation results show that jack-knife and snaking behaviour is eliminated and the appropriate filling-oil pressure for this ASV is confirmed at 1.0 MPa.